RADIATIVE TRANSFER THEORY FOR ESTIMATION OF THE SEISMIC MOMENT - Sens-Schönfelder C.; Wegler U. (My University, 2006)
We propose a new technique to obtain source spectra and seismic moments of regional earthquakes from envelopes of seismic coda. As compared to existing methods, our approach is based on a physical model of the scattering process that produces the seismic coda. This allows the direct estimation of source parameters, without the necessity to fix proportionality coefficients with reference events. We see an appreciable advantage because the method is independent of the output from other techniques, such as reference events provided by moment inversions. The main component of our method is a joint inversion of the seismic records for source and site parameters, as well as for medium parameters assuming isotropic sources and isotropic, acoustic scattering in a half-space. The method is tested with recordings of 11 earthquakes (4 ≤ Ml ≤ 6) by the German Regional Seismic Network at epicentral distances less than 1000 km. We invert the traces in eight frequency bands between 0.2 and 24 Hz and demonstrate that our estimates of the seismic moment are in good agreement with values obtained in independent studies using waveform inversion techniques. In fact our estimates of the seismic moment are better than approximations obtained from local magnitudes using empirical relations specifically derived for the region under study. The parameters that describe the scattering medium are mean free path that we found to average around 690 km and the intrinsic quality factor for which we obtain IQ = 500 below 3 Hz. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CODA; RADIATIVE TRANSFER THEORY; SCATTERING; SEISMIC MOMENT